The oral sensory structures of Thaliacea (Tunicata) and consideration of the evolution of hair cells in chordata. Issue 12 (19th June 2013) - Caicci, Federico; Gasparini, Fabio; Rigon, Francesca; Zaniolo, Giovanna; Burighel, Paolo; Manni, Lucia
<x xml:space="preserve">Abstract</x> We analyzed the mouth of three species, representative of the three orders of the class Thaliacea (Tunicata)—Pyrosoma atlanticum (Pyrosomatida), Doliolum nationalis (Doliolida), and Thalia democratica (Salpida)—to verify the presence of mechanoreceptors, particularly hair cells. In vertebrates, hair cells are well‐known mechanoreceptors of the inner ear and lateral line, typically exhibiting an apical hair bundle composed of a cilium and stereovilli but lacking an axon. For a long time, hair cells were thought to be exclusive to vertebrates. However, evidence of a mechanosensory organ (the coronal organ) employing hair cells in the mouth of tunicates, considered the sister group of vertebrates, suggests that tunicate and vertebrate hair cells may share a common origin. This study on thaliaceans, a tunicate group not yet investigated, shows that both P. atlanticum and D. nationalis possess a coronal organ, in addition to sensory structures containing peripheral neurons (i.e., cupular organs and triads of sensory cells). In contrast, in T. democratica, we did not recognize any oral multicellular sensory organ. We hypothesize that in T. democratica, hair cells were secondarily lost, concomitantly with the loss of branchial fissures, the acquisition of a feeding mechanism based on muscle activity, and a mechanosensory apparatus based on excitable epithelia. Our data are consistent with the hypothesis that hair cells were present in the common ancestor of tunicates and vertebrates, from which hair cells progressively evolved. J. Comp. Neurol. 521:2756–2771, 2013. © 2013 Wiley Periodicals, Inc.